High melphalan exposure is associated with improved overall survival in myeloma patients receiving high dose melphalan and autologous transplantation. (27th April 2016) - Nath, Christa E.; Trotman, Judith; Tiley, Campbell; Presgrave, Peter; Joshua, Douglas; Kerridge, Ian; Kwan, Yiu Lam; Gurney, Howard; McLachlan, Andrew J.; Earl, John W.; Nivison‐Smith, Ian; Zeng, Lihua; et al.
Abstract : Aim: High dose melphalan (HDM) and autologous stem cell transplantation (ASCT) retains a central role in the treatment of myeloma. The aim of this study was to determine whether HDM exposure (area under the concentration vs . time curve, AUC), is significantly associated with transplant outcomes. Methods: Melphalan concentrations were measured in six to 11 plasma samples collected after HDM (median 192 mg m – 2 ) to determine melphalan AUC for a total of 114 patients. Binary logistic regression was used to assess whether melphalan AUC was associated with severe (≥ grade 3) oral mucositis. Multivariate Cox regression was used to assess whether melphalan AUC was significantly associated with time to progression, progression‐free survival and overall survival (OS). Results: Melphalan AUC ranged from 4.9 to 24.6 mg l –1 h, median 12.84 mg l –1 h. Melphalan AUC above the median was a risk factor for severe mucositis (HR 1.21, 95% CI 1.06, 1.38, P = 0.004) but was also associated with significantly improved overall survival (OS) (HR 0.40, 95% CI 0.20, 0.81, P = 0.001), with an estimated median survival of 8.50 years vs . 5.38 years for high vs . low AUC groups. Multivariate analysis did not identify melphalan AUC as being significantly associated with time to progression or progression‐free survival. Conclusions: This large scale pharmacodynamic analysis of HDM demonstrates that high melphalan exposure is associated with improved survival, with an acceptable increase in transplant toxicity. These results suggest studies targeting a higher AUC are warranted in patients undergoing HDM and ASCT for myeloma.